An iterative goal programming approach for solving fuzzy multiobjective integer linear programming problems - Saad, Omar M. (Applied mathematics and computation, 2005)
This paper presents an iterative goal programming approach for solving fuzzy multiobjective integer linear programming problems. These problems involve fuzzy parameters in the right-hand side of the constraints. The concept of α-level set of these fuzzy parameters is introduced with the definition of their membership function. A solution algorithm is described in sequential steps to solve the formulated model. The suggested approach in this paper is mainly based on the iterative goal programming technique together with Gomory cuts. An illustrative numerical example is given to clarify the theory and the solution algorithm.